An analysis of type F2 software measurement standards for profile surface texture parameters - Todhunter, Luke D.; Leach, Richard K.; Lawes, Simon; Blateyron, François (IOP Publishing, 2017)
This paper reports on an in-depth analysis of ISO 5436 part 2 type F2 reference software for the calculation of profile surface texture parameters that has been performed on the input, implementation and output results of the reference software developed by the National Physical Laboratory (NPL), the National Institute of Standards and Technology (NIST) and Physikalisch-Technische Bundesanstalt (PTB). Surface texture parameters have been calculated for a selection of 17 test data files obtained from the type F1 reference data sets on offer from NPL and NIST. The surface texture parameter calculation results show some disagreements between the software methods of the National Metrology Institutes. These disagreements have been investigated further, and some potential explanations are given.